A green and cost-effective approach for the efficient conversion of grape byproducts into innovative delivery systems tailored to ensure intestinal protection and gut microbiota fortification. (August 2022) - Perra, Matteo; Manca, Maria Letizia; Tuberoso, Carlo I.G.; Caddeo, Carla; Marongiu, Francesca; Peris, Josè Esteban; Orrù, Germano; Ibba, Antonella; Fernàndez-Busquets, Xavier; Fattouch, Sami; Bacchetta, Gianluigi; Manconi, Maria
Abstract: According to circular economy, wine-making by-products represent a fascinating biomass, which can be used for the sustainable exploitation of polyphenols and the development of new nanotechnological health-promoting products. In this study, polyphenols contained in the grape pomace were extracted by maceration with ethanol in an easy and low dissipative way. The obtained extract, rich in malvidin-3-glucoside, quercetin, procyanidin B2 and gallic acid, was incorporated into phospholipid vesicles tailored for intestinal delivery. To improve their performances, vesicles were enriched with gelatine or a maltodextrin (Nutriose®), or their combination (gelatine-liposomes, nutriosomes and gelatine-nutriosomes). The small (~147 nm) and negatively charged (~ −50 mV) vesicles were stable at different pH values mimicking saliva (6.75), gastric (1.20) and intestinal (7.00) environments. Vesicles effectively protected intestinal cells (Caco-2) from the oxidative stress and promoted the biofilm formation by probiotic bacteria. A preliminary evaluation of the vesicle feasibility at industrial levels was also performed, analysing the economic and energetic costs needed for their production. Highlights: Valorization of grape pomace by the extraction of the main polyphenols Incorporation of the extract into innovative phospholipid vesicles Evaluation of the stability of the extract containing vesicles at different pHs Protective effect of vesicles against oxidative stress induced in intestinal cells Probiotic effect of formulations on gut microbiota